Film “Bumi Itu Bulat” Sebagai Pesan Dakwah Dalam Menanamkan Nilai-Nilai Toleransi Beragama - Noviana, Gita Putri (Al-Hikmah: Jurnal Dakwah dan Komunikasi, 2024)
This research discusses the message of da'wah in instilling the values ​​of religious tolerance in the film "Bumi Itu Bulat". The aim of this research is to find out the da'wah message and its implementation in the film "Bumi Itu Bulat". The research method used is qualitative with a type of literature research (Library Research) with Roland Barthes' semiotic analysis approach, namely a method that aims to research and study research objects by providing signs with the meaning of denotations and connotations. The results of this research show that there are several da'wah messages contained in the film "Bumi Itu Bulat" namely in the form of aqidah, sharia, morals that make humans tolerant of religious differences. In the film "Bumi Itu Bulat" researchers can take the results from the da'wah messages contained in such as mutual help, mutual respect and acceptance of religious freedom so that they can be implemented in the social life of society. Thus, differences do not become a barrier for anyone to connect with followers of other religions.